Countdown to Crisis : The Coming Nuclear Showdown With Iran - Timmerman, Kenneth R. (New York Crown Forum, 2005)
Examines the growing national security threat involving the nuclear capabilities of Iran, providing an exposé of the intelligence blunders and foreign policy decisions that have increased the threat.
Include Index
Keywords: Military policy -- Nuclear weapons -- World politics